Successful treatment of hemorrhagic bullous Henoch‐Schonlein purpura with intravenous immunoglobulins. Issue 1 (18th December 2018) - Mauro, Angela; Mauro, Salvatore; Rega, Roberto; Martemucci, Luigi; Sottile, Rita
Abstract: Henoch‐Schonlein purpura (HSP) is the most common systemic vasculitis in childhood. There is no consensus about the management for isolated cutaneous manifestations in HSP. We describe a case of HSP presenting with severe skin lesions that did not respond to standard therapy with corticosteroids. The 11‐year‐old child was treated with intravenous immunoglobulins, which induced rapid and persistent resolution of symptomatology.